Overcoming vulnerability: channel design strategies to alleviate vulnerability in customer journeys - Wünderlich, Nancy V. (2020)
Research has shown that any individual consumer, regardless of membership in any particular class, may experience vulnerability in the marketplace. While studies have identified core determinants of customer vulnerability states and perceptions and outlined their impact on consumers and firms, there is little research on how channel design, as part of service design strategies, can be employed to alleviate or prevent states and perceptions of vulnerability. This study extends the current literature on customer vulnerability by developing a framework that delineates determinants and consequences of vulnerability that manifest in problems of accessing or processing resources. We outline three relevant channel design strategies that service providers might employ to alleviate vulnerability: (1) flexibility through multiple multichannel paths, (2) guidance through constrained channel paths and (3) proactive initiation of interactions. Additionally, we propose a future research agenda and offer recommendations for managerial practice regarding how to identify customer vulnerability and employ countermeasures.